Fundamentals of theoretical physics: - Venger, E. F.; Gryban, V. M.; Melnichuk, O. V. (Akademperiodyka, 2016)
In the brief course of theoretical physics, the concepts, formulations, and laws of classical electrodynamics, relativity theory, thermodynamics, and statistical physics are expounded. The course is intended for high school students.
A tutorial